Upscaling climate-smart agriculture practices: working with Farmers’ Field and Business Schools and Village Savings and Loan Associations in rural Tanzania - Pamuk, Haki; Muijlwijk, Miriam van; Wattel, Cor; Deering, Karl; Asseldonk, Marcel van (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This is the first of two Info Notes that summarize research findings on upscaling climate-smart agriculture (CSA) practices among small-scale farmers in rural Tanzania through community-based learning processes and platforms, mainly targeting women farmers. The second Info Note – Gender considerations in the promotion of climate-smart agriculture practices: Evidence from rural Tanzania – summarizes findings on the gender dimensions of promoting CSA practices. This first Note focuses on findings concerning the profitability of CSA practices and the effect of community-based learning processes and platforms on upscaling the adoption of CSA practices. The Note begins with the study background, main concepts, and methodology before presenting and discussing main research results and providing recommendations.